The woman dies - Matsuda, Aoko, 1979- (Europa Editions, 2025)
"In The Woman Dies, renowned author Aoko Matsuda approaches often-thorny subjects such as sexism, prejudice, the normalizing effect of violence against women on screen, or the aesthetics associated with technology, with an inventiveness and quirky humor that keep these stories on the thrilling cusp between seriousness and levity. Wordplay evolves into something much more complex, inanimate objects are endowed with their own point of view, and hard-hitting feminist stances are conveyed with a dry, detached humor that makes them even more undeniable. Not so much a rollercoaster ride, rather an entire theme park, The Woman Dies is an out-of-the ordinary space readers will step into with feelings of wonder and discombobulation in equal parts."--